Changes in correlation characteristics of time consumption and mind-reading performance in pre-onset and post-onset psychosis. (April 2018) - Zhang, TianHong; Xu, LiHua; Cui, HuiRu; Tang, YingYing; Wei, YanYan; Tang, XiaoChen; Liu, XiaoHua; Cao, XinMei; Li, ChunBo; Wang, JiJun
Abstract: There is a strong correlation between neurocognition and social cognition. However, none of these studies have examined the key role of time consumption during social cognition tasks. Participants included 84 individuals with clinical high risk of psychosis (CHR), 95 healthy controls (HC), and 66 case controls (schizophrenia patients, SZ), who were assessed through the Reading-Mind-in-Eyes Tasks (RMET) with computerized recording of the response time (RT). Neurocognitive tests were also performed for the HC and CHR groups. A comparison of RMET performance revealed significantly lower scores in the SZ group compared to the HC group, with CHR individuals scoring between these two. However, both CHR and SZ subjects spent almost twice as long of the time on RMET compared to the HC subjects. Significant positive correlation was found between RMET accuracy and RT, though only in SZ patients. Taking the RT into consideration, the RMET performances were impacted by different neurocognition domains. Our findings provide new evidence about how time consumption in mind-reading may impact the relationship between social cognition and neurocognition, and we discuss the potential importance of recording the response time during social cognition assessment in individuals with early psychosis. Highlights: 66 with schizophrenia(SZ), 84 with clinical high risk(CHR) of psychosis and 95 well matched healthy controls were recruited. CHR subjects performed better at emotional recognition than SZ patients, they showed similar time consumption. Different patterns were found in the relationship between response time and accuracy in emotion recognition across groups. Response time in correct emotion recognition among the three groups are different to patterns seen in incorrect responses.